Robust evaluation of superabsorbent polymers as an internal curing agent in cementitious composites - Danish, Aamar; Mosaberpanah, Mohammad Ali; Salim, Muhammad Usama (Journal of materials science, 2021)
The internal curing of cementitious composites (CCs) has been a subject of supreme importance for the past few years. Although superabsorbent polymers (SAPs) have been utilized in several industries like sanitary, agriculture, and medical, their usability as an internal curing agent to counteract self-desiccation of CC is quite new. In consideration of ongoing demand and usability of SAP, this review article comprehensively discusses the properties and performance of SAP in internally cured CC such as cement paste, mortar, and concrete. The properties of SAP documented include absorption, swelling, and desorption. In addition, the effect of SAP on shrinkage (chemical, plastic, autogenous and drying), rheological (workability, slump, and viscosity), mechanical (compressive, tensile, and flexural strength), and durability (permeability and frost resistance) properties has been extensively discussed. Furthermore, after an in-depth analysis of the mentioned topics, this article gives critical note toward the effective use of SAP in CC.